2007
DOI: 10.1111/j.1478-5153.2007.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Noise levels in a general intensive care unit: a descriptive study

Abstract: The aim of this small-scale study was to measure, analyse and compare levels of acoustic noise, in a nine-bedded general intensive care unit (ICU). Measurements were undertaken using the Norsonic 116 sound level meter recording noise levels in the internationally agreed 'A' weighted scale. Noise level data were obtained and recorded at 5 min over 3 consecutive days. Results of noise level analysis indicated that mean noise levels within this clinical area was 56.42 dB(A), with acute spikes reaching 80 dB(A). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
52
0
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 30 publications
7
52
0
14
Order By: Relevance
“…En düşük gürültü seviyesi olan 50 dB, DSÖ tarafından önerilen maksimum düzeyden %25 daha yüksek kaydedilmiştir (21).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En düşük gürültü seviyesi olan 50 dB, DSÖ tarafından önerilen maksimum düzeyden %25 daha yüksek kaydedilmiştir (21).…”
Section: Discussionunclassified
“…Oysa yoğun bakımlarda yalnızca kardiyak monitörlerin ses seviyelerinin 72-77 dB kadar uzandığı bilinmektedir. Bu durum yoğun bakım ünitelerinin gürültü açısından sıkıntılı bir bölge olduğunu ortaya koymaktadır (7).…”
Section: Introductionunclassified
“…A Organização Mundial de Saúde (OMS) reconheceu que o ruído pode causar danos à saúde das pessoas expostas a ele, como: perturbar o trabalho, o descanso, o sono, a comunicação dos seres humanos, prejudicar a audição e causar reações psicológicas, fisiológicas e patológicas nos indivíduos expostos (6) . Entre vários danos fisiológicos, o ruído pode provocar distúrbios cardiovasculares, redução da saturação arterial de oxigênio, perda auditiva, aumento de secreção gástrica, estimulação da hipófise e adrenal, alteração do sono fisiológico, imunossupressão e redução da cicatrização (7) . Vários estudos têm demonstrado a frequência e importân-cia do ruído no ambiente da UTI (8) , embora a maioria dos estudos seja em UTIs neonatais ou pediátricas (1) .…”
unclassified
“…14 Both patients and members of critical care health teams generally acknowledge that noise levels in the ICU seem high, and studies confirm this notion. 7,15,16 More specifically, the World Health Organization guidelines 17 for noise levels in hospitals specify that the maximum level of sound events during the night should not exceed 40 dB indoors and that sound levels in rooms in the hospital should be 30 dB LAeq, with a maximum level of 40 dB during the night. In addition, because patients have decreased ability to cope with stress, LAeq SPLs should not exceed 35 dB in most rooms in which patients are being treated or observed.…”
mentioning
confidence: 99%
“…As a reference, 60 dB(A) is about the S leep disruption in intensive care units (ICUs) is common 1 and is detrimental to patients' health and recovery. 2 Causes of the disruptions include necessary medical interventions, such as measurement of vital signs and checking of equipment 3 ; disruptions due to pain, medications, and stress 4,5 ; staff interactions with other patients and one another 6,7 ; environmental light 8 ; and noise. [9][10][11] In a review of the literature, Xie et al 12 reported that between 17% and 57.6% of arousals and awakenings are due to noise.…”
mentioning
confidence: 99%